(untitled) - Joseph D Bronzino (Boston, Massachusetts, 1986)
This book provides an integrated, interdisciplinary context for understanding modern techniques in the design, development, and application of biomedical instrumentation. To achieve these objectives, the enficient depth to let the reader understand the overall clinical and engineering problems being addressed
Keywords: biomedical engineering - trends,computers,medical instruments and apparatus,biomedical engineering